Human Pluripotent Stem Cells: Applications and Challenges in Neurological Diseases - HIBAOUI, Youssef; Feki, Anis (Frontiers in Physiology, 2012)
The ability to generate human pluripotent stem cells (hPSCs) holds great promise for the understanding and the treatment of human neurological diseases in modern medicine. The hPSCs are considered for their in vitro use as research tools to provide relevant cellular model for human diseases, drug discovery and toxicity assays and for their in vivo use in regenerative medicine applications. In this review, we highlight recent progress, promises and challenges of hPSC applications in human neurological disease modelling and therapies.